The Portuguese ‘New State’ and the Diffusion of Authoritarian Models in Interwar Latin America - Pinto, Antonio Costa (2021)
As an authoritarian ‘gravity centre’ in the interwar period, the Portuguese New State was not the product of strong propaganda or power capacity. Its force of attraction derived, essentially, from having an international means of diffusion: important segments of the Catholic Church's organizations, its associated intellectual politicians, and particularly from having led a corporatist and authoritarian political system model. How and why did Salazar's New State inspire some of the new political institutions proposed by radical right-wing elites or created by many of these regimes? This article tackles this issue by adopting a transnational and comparative research approach, paying particular attention to the primary mediators of its diffusion and analyzing institutional reform processes in selected processes of crises and transitions to authoritarianism in Latin America.